Access to Justice in Ontario, 1985-1988 - Bogart, W.A. ([Verlag nicht ermittelbar], 1992)
This data collection, which was designed to assess experiences with the Ontario, Canada, civil justice system, is a replication and extension of a survey conducted by the Civil Litigation Research Project at the University of Wisconsin. Interviews were conducted with the heads of households. Questions were asked about the nature of the problem, e.g., auto accident, work injury, discrimination, problems with landlord, violations of privacy, or victimization. Questions were also asked about actions taken in response to the problem, such as whether a lawyer was contacted, reasons for not contacting a lawyer, whether non-lawyer assistance was sought, whether a claim was made, and reasons for not making a claim. Finally, questions were asked about the household's experience with the Ontario justice system if a claim was made, including whether there was a trial or a hearing, how much the lawyer charged, evaluation of the result, satisfaction with the result, evaluation of the cost, perceived delay, agreement reached, and compensation awarded. Major demographic variables include age, occupation, number of persons in household, language, ethnic background, religion, education, and family income.